PEMBELAJARAN FIQIH BERBASIS E-LEARNING DI ERA NEW NORMAL DI MTS NURUL HIDAYAH ANDONG BOYOLALI - Nur Rofiq; Sigit Tri Utomo; Siti Shofiyati (Wahana Islamika: Jurnal Studi Keislaman, 2021)
The development of information technology in the digital era is very influential on the current learning system, especially during the current New Normal. Seen based on the shift in learning from teacher-centered learning to student-centered learning. The learning system used to still use conventional methods or teacher-centered learning where students mostly listened to explanations or explanations of the teacher's material in front of the class and did the assignments given if the teacher distributed practice questions to students. Learning through e-learning is an innovation in the world of education that is expected to improve the quality of education and become a means of continuous learning during the Covid-19 pandemic. The research uses a qualitative method with a case study approach related to e-learning based fiqh learning in the new normal era at Mts Nurul Hidayah Andong Boyolali. Collecting data by observation, interviews and documentation. Analysis of the data using deductive by drawing conclusions. The results showed that the e-learning based fiqh learning process implemented at Mts Al-Hidayah Andong Boyolali by using the E-learning application there were supporting factors so that this learning could be implemented, including the teacher's ability to guide students to be more active and creative; provide space for students to get used to asking questions and expressing opinions, and provide learning resources. In addition to these supporting factors, there are also inhibiting factors, including Students having difficulty using e-learning based learning due to limited internet quota and difficulties in accessing the internet network; students are not fully active in the process of learning fiqh; and difficulties in managing learning time. With e-learning, learning fosters enthusiasm in learning even without face-to-face so that the material obtained can be absorbed optimally